Development of Islamic Religious Education Textbooks Based on Equal Values in the Understanding of Moderate Islam - Alfariza, Agus Aziz; Zulfah, Machnunah Ani; Mahmudi, Mahmudi (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
Textbooks One of the components of the learning system that plays an important role in achieving Standard Competencies and Basic Competencies is textbooks. Textbooks are books used as textbooks in certain fields of study, which are standard books compiled by experts in their fields for instructional purposes and objectives, which are equipped with teaching tools that are harmonious and easy to understand by users in schools and universities so that they can support a teaching program. The important elements in the definition of textbooks are as follows: (1). textbooks are textbooks intended for students at a certain level. (2). Textbooks are always related to certain subjects. (3.) Textbooks are standard books. (4). Textbooks are written for certain instructional purposes. (5). Textbooks are written to support a certain teaching program. (Arifin, 2009) With the existence of textbooks, teaching and learning activities in schools become smoother and more effective. With the existence of textbooks, students' basic skills and knowledge have been obtained before entering the classroom so that during the classroom they can be used for activities to strengthen memory, understand concepts, think critically, and develop knowledge.